Metal cluster composite graphite felt electrode in all-vanadium redox flow battery and preparation method and application thereof
Patent Information
- Application Number
- CN202610980534.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-02
- Publication Date
- 2026-10-30
AI Technical Summary
然而,石墨毡在电化学活性方面仍存在不足,因此对其进行改性以提升性能是十分必要的
本发明提供的石墨毡电极可以通过金属簇的形成量调控氧化还原反应过程,金属簇的形成提高了催化活性。改性后的石墨毡电极亲水性和电催化活性较好,减少了全钒液流电池电极的极化,有效提高全钒液流电池的容量和能量效率。本发明石墨毡电极改性方法所需成本较低,反应简单易行,易于大规模生产过程。
Smart Images

Figure CN123017991A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of vanadium redox flow battery electrode technology, and particularly to a metal cluster composite graphite felt electrode for vanadium redox flow batteries, its preparation method, and its application. Background Technology
[0002] Metal nanoclusters are relatively stable aggregates composed of several to hundreds of metal atoms. As a novel system with sizes between the macroscopic and microscopic scales, they possess many unique properties. These properties primarily stem from two typical cluster effects: the size effect and the surface effect. The size effect, within this scale range, leads to the quantization of the material's band structure. In recent years, metal nanocluster catalysis has emerged as a rapidly rising research topic, injecting new vitality into the frontiers of heterogeneous catalysis research over the past decade. A key characteristic of metal nanoclusters is the anchoring of metal sites onto a solid support, maximizing the dispersion and utilization of metallic properties. The active sites of metal nanoclusters can effectively activate numerous molecules, thus exhibiting remarkable catalytic activity in many catalytic reactions.
[0003] Vanadium redox flow batteries have become a highly mature flow battery technology due to their superior safety, large energy storage capacity, and long charge-discharge cycle life. Vanadium redox flow batteries provide a site for redox reactions through electrodes, enabling the interconversion of active materials in different valence states, thereby effectively realizing the conversion between electrical energy and chemical energy.
[0004] Electrodes are the core components of vanadium redox flow batteries. The conductivity of the electrode material and its contact area with the electrolyte are two key factors affecting the overall battery performance. Graphite felt is a widely used electrode material, possessing not only good acid resistance but also an internal porous structure that supports electrolyte flow. However, graphite felt still has shortcomings in electrochemical activity, making modification to improve its performance essential. By modifying graphite felt fibers with metal oxides anchored to metal clusters, the abundant active sites can effectively enhance the electrode's electrocatalytic activity, thereby improving the battery's charge-discharge performance. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention provides a metal cluster composite graphite felt electrode for an all-vanadium redox flow battery, its preparation method, and its application.
[0006] To achieve this technical objective, the present invention adopts the following solution: In a first aspect, the present invention provides a method for preparing a metal cluster composite graphite felt electrode in a vanadium redox flow battery, comprising the following steps: S1. Add P25 (nano-titanium dioxide) to a beaker containing an aqueous sodium hydroxide solution and stir continuously until homogeneous. Transfer the mixture to a stainless steel high-pressure reactor lined with polytetrafluoroethylene and place it in an electrically heated constant-temperature drying oven for heating, then allow it to cool naturally to room temperature. Wash with deionized water until neutral. Etch the precipitate three times with an acid solution, 1 hour each time, wash with deionized water until neutral, collect by centrifugation, and dry at 60 °C for at least 12 hours. Finally, calcine the precipitate in a muffle furnace at 400 °C for 1 hour to obtain porous titanium dioxide nanowires. S2. The prepared titanium dioxide nanowire powder was dispersed in a dimethylimidazole aqueous solution. After stirring evenly, a bismuth nitrate-mannitol mixed aqueous solution was injected into the above dispersion solution, and the mixture was continuously stirred at room temperature. The precipitate was then washed several times with deionized water and ethanol, and dried at 60 °C for at least 12 h. Finally, the precipitate was placed in a tube furnace and heated to 450 °C for 1 h at a heating rate of 5 °C / min under an argon atmosphere to generate bismuth cluster-anchored titanium dioxide catalyst powder. S3. Bismuth cluster-anchored titanium dioxide powder and N,N-dimethylformamide solution are ultrasonically mixed evenly and then modified into graphite felt electrode. The mixture is then dried in an 80 ℃ drying oven to obtain metal cluster composite graphite felt electrode.
[0007] Preferably, in step S1, the heating temperature of the mixture is 130~150 ℃, the heating rate is 3~5 ℃ / min, and the holding time is 48~96 h; the etching acid solution is dilute hydrochloric acid; and the heating rate for calcining the precipitate is 2 ℃ / min.
[0008] Preferably, in step S2, the total mass concentration of the bismuth nitrate-mannitol mixed aqueous solution is 0.5 mg / μL, wherein the mass ratio of Bi(NO3)3 to mannitol is 1:1, the volume of the mixed aqueous solution is 40~160 μL, and the volume of a single use is 35~45 μL.
[0009] Preferably, in step S3, the volume of the graphite felt electrode is 4.5 cm³. 3 The volumetric loading of bismuth cluster-anchored titanium dioxide powder is 3–5 mg / cm³. 3 .
[0010] Secondly, the present invention provides a metal cluster composite graphite felt electrode for a vanadium redox flow battery, which is prepared by the aforementioned method for preparing a metal cluster composite graphite felt electrode for a vanadium redox flow battery.
[0011] Thirdly, the metal cluster composite graphite felt electrode from the aforementioned vanadium redox flow battery is applied to the vanadium redox flow battery.
[0012] Compared with the prior art, the beneficial effects of the present invention are as follows: The graphite felt electrode provided by this invention can regulate the redox reaction process by the amount of metal clusters formed, and the formation of metal clusters improves catalytic activity. The modified graphite felt electrode has good hydrophilicity and electrocatalytic activity, reduces the polarization of the vanadium redox flow battery electrode, and effectively improves the capacity and energy efficiency of the vanadium redox flow battery. The graphite felt electrode modification method of this invention requires low cost, is simple and easy to implement, and is suitable for large-scale production. Attached Figure Description
[0013] Figure 1 These are electron microscope images of the metal clusters in Embodiments 1-3 of the present invention.
[0014] Figure 2 This is the X-ray diffraction pattern of the metal cluster in Embodiment 2 of the present invention.
[0015] Figure 3 This is the X-ray photoelectron spectrum of the metal cluster in Embodiment 2 of the present invention.
[0016] Figure 4 These are the cyclic voltammetry curves of Embodiments 1-3 of the present invention.
[0017] Figure 5 This is a discharge capacity diagram of Embodiment 2 and Comparative Example 1 of the present invention. Detailed Implementation
[0018] To make the objectives, technical solutions, and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments.
[0019] Unless otherwise specified, the experimental methods used in the embodiments and comparative examples of this invention are conventional methods. Unless otherwise specified, the materials and reagents used are commercially available. Example 1
[0020] S1. Add 0.6 g of P25 to a beaker containing 33 mL of NaOH aqueous solution (10 mol / L), stir continuously for 30 min, transfer the mixture to a 50 mL PTFE-lined stainless steel autoclave and place it in a 130 ℃ constant temperature drying oven for 48 h at a heating rate of 5 ℃ / min, then allow it to cool naturally to room temperature. Etch three times with HCl solution (1 mol / L) (1 h each time), wash with deionized water until neutral, collect by centrifugation, and dry in a 60 ℃ oven overnight. Finally, calcine the above precipitate in a muffle furnace at 400 ℃ for 1 h at a heating rate of 2 ℃ / min to obtain porous titanium dioxide nanowires.
[0021] S2. The prepared titanium dioxide nanowire powder (200 mg) was dispersed in 20 mL of 1,2-dimethylimidazole (3 mg / mL) aqueous solution. After stirring for 30 min, 40 μL of a Bi(NO3)3-mannitol mixed aqueous solution with a total mass concentration of 0.5 mg / μL (Bi(NO3)3 to mannitol mass ratio of 1:1) was injected into the above dispersion solution, and the mixture was stirred continuously at room temperature for 3 h. The precipitate was then washed several times with deionized water and ethanol, and dried overnight in a 60 ℃ drying oven. Finally, the precipitate was placed in a tube furnace and treated for 1 h at a heating rate of 450 ℃ and 5 ℃ / min under an argon atmosphere to generate bismuth cluster-anchored titanium dioxide (Bi / TiO2) product.
[0022] S3. 10 mg of bismuth cluster-anchored titanium dioxide powder and 10 mL of N,N-dimethylformamide solution were ultrasonically mixed for 3 h and then modified into a graphite felt electrode. The electrode was then dried in an 80 ℃ drying oven to obtain a metal cluster composite graphite felt electrode. Example 2
[0023] S1. Add 0.6 g of P25 to a beaker containing 33 mL of NaOH aqueous solution (10 mol / L), stir continuously for 30 min, transfer the mixture to a 50 mL PTFE-lined stainless steel autoclave, and place it in a 140 ℃ constant temperature drying oven for 72 h at a heating rate of 5 ℃ / min, then allow it to cool naturally to room temperature. Wash with deionized water until neutral, etch three times with HCl solution (1 mol / L) (1 h each time), wash with deionized water until neutral, collect by centrifugation, and dry in a 60 ℃ oven overnight. Finally, calcine the above precipitate in a muffle furnace at 400 ℃ for 1 h at a heating rate of 2 ℃ / min to obtain porous titanium dioxide nanowires.
[0024] S2. The prepared titanium dioxide nanowire powder (200 mg) was dispersed in 20 mL of 1,2-dimethylimidazole (3 mg / mL) aqueous solution. After stirring for 30 min, 80 μL of a Bi(NO3)3-mannitol mixed aqueous solution with a total mass concentration of 0.5 mg / μL was injected into the above dispersion solution, and the mixture was stirred continuously at room temperature for 3 h. The precipitate was then washed several times with deionized water and ethanol, and dried overnight in a 60 ℃ drying oven. Finally, the precipitate was placed in a tube furnace and treated at 450 ℃ and a heating rate of 5 ℃ / min for 1 h under an argon atmosphere to generate the Bi / TiO2 product.
[0025] S3. 20 mg of bismuth cluster-anchored titanium dioxide powder and 10 mL of N,N-dimethylformamide solution were ultrasonically mixed for 3 h and then modified into a graphite felt electrode. The electrode was then dried in an 80 ℃ drying oven to obtain a metal cluster composite graphite felt electrode. Example 3
[0026] S1. Add 0.6 g of P25 to a beaker containing 33 mL of NaOH aqueous solution (10 mol / L), stir continuously for 30 min, transfer the mixture to a 50 mL stainless steel autoclave lined with polytetrafluoroethylene, and place it in a 150 ℃ electric thermostatic drying oven for 96 h at a heating rate of 5 ℃ / min, then allow it to cool naturally to room temperature. Wash with deionized water until neutral, etch three times with HCl solution (1 mol / L) (1 h each time), wash with deionized water until neutral, collect by centrifugation, and dry in a 60 ℃ oven overnight. Finally, calcine the above precipitate in a muffle furnace at 400 ℃ for 1 h at a heating rate of 2 ℃ / min to obtain porous titanium dioxide nanowires.
[0027] S2. The prepared titanium dioxide nanowire powder (200 mg) was dispersed in 20 mL of 1,2-dimethylimidazole (3 mg / mL) aqueous solution. After stirring for 30 min, 160 μL of a Bi(NO3)3-mannitol mixed aqueous solution with a total mass concentration of 0.5 mg / μL was injected into the above dispersion solution, and the mixture was stirred continuously at room temperature for 3 h. The precipitate was then washed several times with deionized water and ethanol, and dried overnight in a 60 ℃ drying oven. Finally, the precipitate was placed in a tube furnace and treated at 450 ℃ and a heating rate of 5 ℃ / min for 1 h under an argon atmosphere to generate the Bi / TiO2 product.
[0028] S3. 30 mg of bismuth cluster-anchored titanium dioxide powder and 10 mL of N,N-dimethylformamide solution were ultrasonically mixed for 3 h and then modified into a graphite felt electrode. The electrode was then dried in an 80 ℃ drying oven to obtain a metal cluster composite graphite felt electrode. Comparative Example 1
[0029] This comparative example is a blank control group, that is, using untreated blank graphite felt electrodes.
[0030] The metal clusters obtained in each embodiment were characterized, and the graphite felt electrodes prepared in each embodiment and the comparative example were assembled into an all-vanadium redox flow battery for testing.
[0031] Figure 1 a is a scanning electron microscope image of the metal clusters in Example 1 of the present invention. It can be seen that the relatively long size of the titanium dioxide nanowires results in a sparse distribution of bismuth clusters on the titanium dioxide nanowires. Figure 1 b is a scanning electron microscope image of the metal clusters in Example 2 of the present invention, which shows that the bismuth clusters are loaded on titanium dioxide nanowires and are uniformly dispersed. Figure 1 c is a scanning electron microscope image of the metal clusters in Example 3 of the present invention. It can be seen that the titanium dioxide nanowires are short and the bismuth clusters are loaded and aggregated on the titanium dioxide nanowires.
[0032] Figure 2 This is the X-ray diffraction pattern of the product obtained in Example 2 of this invention. Phase analysis showed that characteristic diffraction peaks of Bi2O3 were detected in the product, confirming that the bismuth clusters were successfully loaded onto the titanium dioxide nanowires.
[0033] Figure 3 The X-ray photoelectron spectrum of the product obtained in Example 2 of this invention shows the characteristic double peak of bismuth, indicating that the bismuth cluster exists in a metallic state and is uniformly distributed in the composite material.
[0034] Figure 4 These are the cyclic voltammetry curves of Examples 1-3 of this invention. Example 2 exhibits the most symmetrical redox peak shape and the highest current density at both the oxidation and reduction peaks, indicating that it possesses optimal electrochemical reversibility and charge transfer kinetics performance.
[0035] Figure 5 The diagram shows the discharge capacity of Embodiment 2 and Comparative Example 1 of the present invention. It can be seen that Embodiment 2 has a larger discharge capacity than the blank graphite felt of Comparative Example 1.
[0036] The graphite felts prepared in Examples 1-3 and Comparative Example 1 were respectively assembled into batteries and subjected to charge-discharge tests under the same test conditions. The coulombic efficiency, voltage efficiency, and energy efficiency of the batteries were recorded. The test results are shown in Table 1.
[0037] Table 1. Electrode performance test results of the examples and comparative examples
[0038] As shown in Table 1, the embodiments of the present invention exhibit higher energy efficiency and voltage efficiency compared to the comparative examples. This indicates that the present invention utilizes controlled synthesis temperature and time of 130–150 °C and 48–96 h to form porous titanium dioxide, providing a site for the anchoring of metal clusters. Metal clusters can be formed in 80 μL bismuth nitrate solution (0.5 mg / μL mannitol solution). The metal clusters can be uniformly dispersed on the graphite felt surface. The present invention increases active sites and promotes redox reactions through metal clusters. In Example 1, the metal clusters formed are sparse, making it difficult to provide attachment sites for active materials, thus failing to guarantee the battery's capacity retention. In Example 3, excessive metal clusters form large metal particles, which can clog electrolyte transport channels, resulting in a significant decrease in battery voltage efficiency and energy efficiency.
[0039] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; if these modifications and variations fall within the scope of the claims of the present invention and their equivalents, they should all be considered to be within the protection scope of the present invention.
Claims
1. A method for preparing a metal cluster composite graphite felt electrode in a vanadium redox flow battery, characterized in that, Includes the following steps: S1. Add P25 to an aqueous sodium hydroxide solution and stir until homogeneous. Transfer the mixture to a stainless steel high-pressure reactor lined with polytetrafluoroethylene, heat, and then allow to cool naturally to room temperature. Wash with deionized water until neutral. Etch the precipitate three times with an acid solution for 1 hour each time. Wash with deionized water until neutral. Collect by centrifugation and dry at 60 °C for at least 12 hours. Finally, calcine the precipitate at 400 °C for 1 hour to obtain porous titanium dioxide nanowires. S2. The prepared titanium dioxide nanowire powder was dispersed in a dimethylimidazole aqueous solution. After stirring evenly, a bismuth nitrate-mannitol mixed aqueous solution was injected into the above dispersion solution. The mixture was stirred continuously at room temperature. The precipitate was then washed with deionized water and ethanol and dried at 60 °C for at least 12 h. Finally, the precipitate was heated to 450 °C for 1 h at a heating rate of 5 °C / min under an argon atmosphere to generate bismuth cluster-anchored titanium dioxide catalyst powder. S3. Bismuth cluster-anchored titanium dioxide powder and N,N-dimethylformamide solution are ultrasonically mixed evenly and then modified into graphite felt electrode. The mixture is dried at 80°C to obtain metal cluster composite graphite felt electrode.
2. The method for preparing the metal cluster composite graphite felt electrode in the all-vanadium redox flow battery according to claim 1, characterized in that, In step S1, the mixture is heated to 130~150 ℃, the heating rate is 3~5 ℃ / min, and the holding time is 48~96 h; the etching acid solution is dilute hydrochloric acid; the heating rate for calcining the precipitate is 2 ℃ / min.
3. The method for preparing the metal cluster composite graphite felt electrode in the all-vanadium redox flow battery according to claim 1, characterized in that, The total mass concentration of the bismuth nitrate-mannitol mixed aqueous solution in step S2 is 0.5 mg / μL, and the volume used is 40~160 μL.
4. The method for preparing the metal cluster composite graphite felt electrode in the all-vanadium redox flow battery according to claim 1, characterized in that, In step S3, the volume of the graphite felt electrode is 4.5 cm³. 3 The volumetric loading of bismuth cluster-anchored titanium dioxide powder is 3~5 mg / cm³. 3 .
5. A metal cluster composite graphite felt electrode for a vanadium redox flow battery prepared by the method described in any one of claims 1-4.
6. The application of the metal cluster composite graphite felt electrode in the vanadium redox flow battery according to claim 5.
